Analisis Pengendalian Persediaan Bahan Baku dengan Mengggunakan Medote Material Requirement Planning pada Home Industri Roti Djadwa di Demangan Boyolali - Yulfina Putri Wahyuningrum; Erni Widajanti (Universitas 45 Surabaya, 2024)
Home industry DJADWA Bread is a company operating in the food sector that focuses on making bread. Inventory is one of the most important assets in a company, because on the one hand the company can reduce costs by reducing inventory and on the other hand it can cause production to stop and consumer satisfaction to decrease. The aim of this research is to analyze the efficiency of inventory costs for raw materials for flour, sugar and butter using the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ) and Period Order Quantity methods. (POQ). Theresearch results show that the total raw material inventory for Material Requirement Planning, especially using the Economic Order Quantity method, will obtain the most efficient raw material inventory costs. This is proven by the total cost of raw material inventory according to the policy of IDR 4,599,790 while Lot For Lot is IDR 3,600,000, Economic Order Quantity is IDR 1,436,338 and the Period Order Quantity method is IDR 3,600,000, then from the results of the total inventory calculation raw materials, then the MRP Material Requirement Planning method uses the Economic Order Quantity (EOQ) technique, because by using the Economic Order Quantity (EOQ) technique Home Industry DJADWA bread in Demangan can achieve the most efficient raw material purchasing costs compared to current company policies and LFL and POQ methods.